The Effect of Company Size and Independent Commisioner Composition on Carbon Emissions Disclosure Before and After the Carbon Tax Regulation News - Mawatish Aina Asmi Hasan; Waluyo Waluyo; Yananto Mihadi Putra; Fransisca Listyaningsih Utami (Business, Management & Accounting Journal (BISMA), 2026)
This study aims to evaluate the influence of company size and the composition of independent commissioners on the level of carbon emissions disclosure. The research subjects include companies in the energy, transportation, and construction sectors in Indonesia. The sample consists of 19 companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2023, with a total of 114 annual observations. The sample selection was conducted using purposive sampling. The analysis methods employed include multiple linear regression and paired sample t-tests, with data processing conducted using SPSS software version 25.0. The multiple linear regression test was supplemented with descriptive statistical analysis, classical assumption tests, and hypothesis testing, while the paired t-test was accompanied by normality and homogeneity tests. The research findings indicate that company size and the composition of independent commissioners significantly influence carbon emissions disclosure, both before and after the announcement of carbon tax regulations. Additionally, there are significant differences in the level of emissions disclosure between the periods before and after the announcement of such regulations.